Exploring the impact of nutrition and lifestyle in the pathogenesis of acne vulgaris - Alsindi, Zahra; Alharbi, Raghad; Alhadi, Enas; AlRadhwan, Nafisah; Aljahdali, Wasan; Alghamdi, Sami; Alghamdi, Abdulrahman; Samargandi, Sarah; Abualqassim, Mohammed; Baabdullah, Ahmed; Alzahrani, Khames (Saudi Medical Horizons Journal, 2025)
Introduction: Acne vulgaris is a common chronic inflammatory skin condition that affects adolescents and young adults. Its development is influenced by hormonal, microbial, and environmental factors. Emerging research suggests that lifestyle and nutrition may significantly affect acne severity and prevalence, but there is limited evidence from the Saudi population. Objectives: To determine the prevalence of acne vulgaris and evaluate associated dietary and lifestyle risk factors among individuals in Saudi Arabia. Methods: A cross-sectional survey was conducted across Saudi Arabia between July and December 2024. Participants aged 18 and above with current or past acne vulgaris were recruited through social media platforms. A validated questionnaire assessed demographic data, lifestyle habits (hydration, sleep, physical activity, smoking), dietary patterns (fast food, dairy, chocolate), and acne history. Data were analyzed using SPSS version 21, with p-values ≤ 0.05 considered statistically significant. Results: A total of 559 participants were included, with 65.3% females and 34.7% males. Overall, 45.6% of participants were aged 25 years or below. One-third consumed less than 1 liter of water daily, and 42.6% reported no physical activity. Acne onset commonly occurred between ages 11 and 20, with moderate severity being most prevalent. Statistically significant associations were found between acne treatment-seeking behavior and water intake, physical activity, and demographic variables. Discussion: The findings support the role of modifiable lifestyle factors in acne pathogenesis. Hydration, exercise, and dietary habits may influence both development and management of acne vulgaris. Conclusion: Lifestyle and dietary behaviors significantly impact acne vulgaris. Public health efforts and patient education targeting these factors may improve acne outcomes in the Saudi population.